2011
DOI: 10.1002/anie.201104367
|View full text |Cite
|
Sign up to set email alerts
|

High Photocurrent in Silicon Photoanodes Catalyzed by Iron Oxide Thin Films for Water Oxidation

Abstract: Silicon splits: The application of silicon to water oxidation is limited due to unfavorable interface properties. However, these can be circumvented by using a high-performance silicon photoanode with a catalytically active iron oxide thin film (see picture). This approach results in photocurrents as high as 17 mA cm(-2) under 1 sun and zero overpotential conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
2
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 34 publications
4
53
2
3
Order By: Relevance
“…[30] On the other hand, under light illumination and positive bias, the positive-charged inversion layer (induced by alkaline electrolyte) beneath the SiO x /Si interface can repel electrons into the Si substrate, reducing the charge recombination in the inversion Extensive efforts have been devoted to the development of clean and renewable energy sources because of the increasing energy demands and environmental issues. [11] To address this problem, a variety of metal and/or oxide coatings (e.g., doped SiO x , [12] transparent conductive oxides, [13] transition metals, and their oxides [9,[14][15][16][17][18][19][20][21][22][23] ) have been explored to protect Si photoanodes. [4,5] However, it is still a great challenge to develop effective techniques for the utilization of solar energy cheaply, conveniently, and efficiently.…”
Section: Doi: 101002/aenm201601805mentioning
confidence: 99%
“…[30] On the other hand, under light illumination and positive bias, the positive-charged inversion layer (induced by alkaline electrolyte) beneath the SiO x /Si interface can repel electrons into the Si substrate, reducing the charge recombination in the inversion Extensive efforts have been devoted to the development of clean and renewable energy sources because of the increasing energy demands and environmental issues. [11] To address this problem, a variety of metal and/or oxide coatings (e.g., doped SiO x , [12] transparent conductive oxides, [13] transition metals, and their oxides [9,[14][15][16][17][18][19][20][21][22][23] ) have been explored to protect Si photoanodes. [4,5] However, it is still a great challenge to develop effective techniques for the utilization of solar energy cheaply, conveniently, and efficiently.…”
Section: Doi: 101002/aenm201601805mentioning
confidence: 99%
“…For example for the Si/Fe 2 O 3 electrodes, Mayer et al have shown the reduction of photoanodic turn-on potential through the dual-absorber nature of the n-Si/n-Fe 2 O 3 junction [18], while Jun et al have reported the photoanodic onset potential decrease due to the catalytic effect of n-Fe 2 O 3 on n-Si [33]. Building full PEC systems based on nanowire (NW) heterojunction photoelectrodes is a promising approach for solar hydrogen production due to unique characteristics of NWs, facile NW fabrication methods, ability to form different NW heterostructures, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Si dominates the current solar cell market mainly because of the low cost in manufacturing highly pure and crystalline substrates [14]. However, when used as a photoanode, it faces critical challenges of corrosion by the electrolyte.…”
Section: Silicon (Si) Photoanodementioning
confidence: 99%